PERTAMBAHAN PERTUMBUHAN BIBIT KELAPA SAWIT (ELAEIS GUINEENSIS JACQ) DI PRE NURSERY AKIBAT PERLAKUAN UREA DAN NPK - Bilter A. Sirait; Agnes Imelda Manurung (Jurnal Darma Agung, 2022)
The purpose of this study was to determine the increasing of Growth of Oil Palm (Elaeis guineensis Jacq) Seedlings in Pre-nursery due to Urea and NPK Treatment. The study used a Completely Randomized Design (CRD) consisting of the first factor Urea fertilizer (U) which consisted of 3 treatment levels, namely U0 = control, U1 = 1.0 g baby polybag-1, and U2 = 2.0g baby polybag-1, while the factor NPK fertilizer (N) consisted of 3 treatment levels, namely N0 = control, N1 = 1.0 g baby polybag-1 and N2 = 2.0 g baby polybag-1. The results showed that with exception for the increase in leaf area, Urea and NPK treatments were not significant for increase of plant height (cm), stem diameter (cm), number of leaves (blades), leaf length (cm) and leaf width (cm), the results were also variative. Furthermore, conclusion of this research is that the higher the dose of urea and NPK fertilizer resulted in a higher increase in leaf area.